Domestic Violence in India: Effects of Education - John Simister and Judith Makowiec (Indian Journal of Gender Studies 2008; 15; 507, 2008)
This article studies domestic violence between husband and wife in India, and attitudes to domestic violence. We use the term `gender-based violence' because some men use violence to control their wives. Data from the Demographic and Health Survey 1998- 2000 has been analysed. This survey includes women in the ages of 15 to 49, in 26 Indian states. We focus only on violence by husbands against wives, ignoring other types of violence (such as a wife being hit by her husband's family, or a man being hit by his wife). Evidence in this paper is consistent with previous research indicating that gender-based violence is very prevalent in India. It seems likely that it is related to whether such violence is seen as acceptable in the perpetrator's family and in the local community. We suggest that there are similarities between the behaviour of some Indian men and the `machismo' values reported in other cultures (especially in Latin America). We confirm previous claims that violence is less common if women and men are well educated; we also note that acceptance of domestic violence appears to be related to the respondent's education level. Thus, we encourage the Governmentof India to prioritise education for both boys and girls.